Implementing Health Apps for Digital Public Health – An Implementation Science Approach Adopting the Consolidated Framework for Implementation Research - Wienert, Julian; Zeeb, Hajo (Frontiers in Public Health, 2021)
Apps are becoming an increasingly important component of modern Public Health and health care. However, successful implementation of apps does not come without challenges. The Consolidated Framework for Implementation Research (CFIR) provides an overarching typology to support the development of implementation theories and the examination of what works where and why in different contexts. The CFIR provides a pragmatic structure for approaching complex, interacting, multi-level and transient states of constructs in the real world: It works on the basis of key constructs from published implementation theories and can be used to guide formative evaluations and build the knowledge base for implementation across multiple studies and settings. In a synthesis of the original English language text describing the CFIR, an attempt was made to break the constructs down into the shortest possible concise descriptions for the implementation of health care apps in a structured, selective process. The listed key constructs should help to develop successful implementation plans and models for health care apps and show the complexity of a successful implementation. The list does not claim to be exhaustive and should be understood as a first attempt of systematization.